Penerapan Discovery Learning Model Dalam Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran Bahasa Inggris - Eni Susilowati (Universitas Muhammadiyah Ponorogo, 2022)
This study aims to determine the increase in student learning outcomes in English subject after the implementation of discovery learning. This research was conducted in two cycles with the research sample being class XI multimedia of SMK Negeri 1 Mlarak in semester I of the 2021/2022 academic year which involved 32 students. The data collection technique consists of student worksheets and observation sheets. Preliminary data shows that students' learning outcomes are below KKM ≥75 with an average student score of only 63 with classical learning completeness of 32 students, only 5 students complete (16%) and 27 students (84%) incomplete. In the first cycle, after applying learning using discovery learning, the average student score increased to 70 with completeness of 11 students (34%). Furthermore, in cycle II after learning using discovery learning was applied there was a slight change with the average score increasing to reach 87 with completeness of 31 students (97%). The results of this study found that the application of discovery learning learning models can improve student learning outcomes in English subjects.